Average ozone vertical distribution at Sodankyla based on the 1988-1991 ozone sounding data - Rummukainen, Markku; Taalas, Petteri; Supperi, Ari; Kyro, Esko (1994)
The study presents the statistical analysis of ozone sonde data obtained at Sodankyla (67.4 deg N, 26.6 deg E) from the beginning of the sounding program on March 1988 to the end of December 1991. The Sodankyla sounding data offers the longest continuous record of the ozone vertical distribution in the European Arctic. In this paper, we present the average ozone partial pressures within each 1 km column obtained for different seasons during the almost four year long period. We believe that the data represented here are useful as an interim reference ozone atmosphere, especially considering the fact that northern Scandinavia has become a popular campaign site for the big international ozone experiments.